Improbidade administrativa e responsabilidade subjetiva na jurisprudência do Tribunal de Justiça do Estado do Maranhão - PINHEIRO, Heron de Jesus Garcez (2018)
This research aims to examine the Justice Court of the State of Maranhão´s case law, regarding the application of the Law of Administrative Improbity (Federal Law 8.429/1992), with special emphasis on the subjective responsibility of public agents. We analyze the historical transformations that provoked the borders of the current democratic states, the theories about the phenomenon of corruption and the interpretations about the patrimonial inheritance pointed to explain the violation to the postulates of administrative probity. Specific theoretical questions about Federal Law nº 8.429/1992 are addressed in order to situate it as a kind of public mismanagement, including behaviors of dishonesty and serious functional inefficiency. Afterwards, we study the discourse of the researched justice institution about the subjective requirements of the administrative misconduct, as well as the concrete criteria of justification of the judgments regarding the mentioned point. The discourse analysis by french line is used as a methodology to verify, in the cases judged by the investigated justice institution and that constitute the corpus of this work, the regularities and ruptures in the treatment of administrative misconduct.